Towards Pay-As-You-Move (PAYM) insurance: The multimodal mobility risk transfer solution - Emer Owens; Barry Sheehan; Martin Mullins; Martin Cunneen; German Castignani; Leandro Masello (Transportation Research Interdisciplinary Perspectives)
Climate change, emissions and carbon–neutral city goals have increased the focus on developing a more diverse socio-environmentally friendly transportation ecosystem. Modern personal mobility incorporates the use of multiple modes of transport per week, or even within the same trip. The transition to sustainable, greener transport is exemplified by the rising popularity of micro-mobility, shared-mobility and electric vehicles. However, current mobility risk-transfer mechanisms do not support modern mobility preferences and travel behaviour. The insurance industry could incentivise sustainable modes of transport by offering innovative risk-transfer solutions. This research proposes Pay-As-You-Move (PAYM) usage-based insurance, a novel transport insurance product for multi-modal mobility. PAYM insurance utilises travel behaviour data gathered from smartphone telematics to detect mobility patterns and determine the corresponding risk of an accident occurring. The proposed risk assessment scheme leverages British road safety data on accident frequencies and severities to quantify a relative risk value for four mobility types and derive an appropriate insurance product. Then, the relative risk of a multi-modal trip is calculated as the product of the mileage, the accident probability and the accident severity per mobility type. Additionally, a control banding risk assessment is presented as a qualitative pricing model for the proposed PAYM product. As civil society looks toward a low-carbon lifestyle, the insurance industry is tasked with adapting transportation insurance offerings to avoid a transport protection gap. This novel usage-based insurance product promotes a range of dependable, frictionless, and greener mobility solutions, benefiting society in our collective efforts to embed sustainability into our daily lives.